A structural equation model to test a conceptual framework of oral health in Japanese edentulous patients with an item weighting method using factor score weights: a cross-sectional study - Eijiro Yamaga; Yusuke Sato; Shunsuke Minakuchi (BMC, 2018)
Abstract Background To investigate Locker's multidimensional model of oral health in Japanese edentulous patients with an item weighting method using factor score weights, which is more accurate than the sum scoring method. A previous study tested Locker's model in edentulous elders in the UK, using empirical evidence from the Short-Form Oral Health Impact Profile (OHIP-14). Investigating the model using the OHIP for edentulous subjects (OHIP-EDENT), which contains 19 items suitable for these patients, may complement that study. Testing Locker's model in Japanese patients may support generalization of the model. Methods A total of 394 patients who were edentulous in both arches and visited the Dental Hospital of Tokyo Medical and Dental University for new complete dentures were recruited. This cross-sectional study had a non-probabilistic sampling design and included the following: data collection; application of the new item weighting method that involves hierarchical confirmatory factor analysis (CFA) to derive factor score weights for each item, using the bootstrap method, to check the significance of the factor score weights; and empirical testing of Locker's conceptual model of oral health in Japanese edentulous patients, using structural equation modelling analysis with the bootstrap method for precise estimations and model generation. Results Factor score weights derived from CFA were significant. After item weighting, the initial model was analyzed and found to have an inconsistent direct path (functional limitation to disability). This path was eliminated from the model and the modified model was re-run. All effects were significant. The model showed acceptable fit on indices including the model chi-squared, standardized root-mean-square residual, root mean-square error of approximation, goodness-of-fit index, comparative fit index, and P-value. Conclusions Our findings showed an empirical fit to Locker's model in Japanese edentulous patients when using the item weighting method, which was more accurate than the sum scoring method. These results could contribute to the generalization of Locker's model. Trial registration The experimental procedures were published in the University hospital Medical Information Network (UMIN) Center (UMINCTR Clinical Trial, Unique trial Number: UMIN000028711).